PWM control for dual two-level inverters - Nguyen, Văn Nhờ; Phan, Thanh Hoàng Anh (Journal of Technical Education Science, 2010)
Many hybrid multilevel inverter topologies have been investigated for simplifying hardware building and reducing cost. This paper introduces dual inverters. One of the actual issues of dual inverters presents an optimised PWM control method. The paper describes a novel PWM control method for dual two-level inverters using carrier based PWM approach. The proposed method has been validated by simulation results and verified by experiment using DSP controller DSPACE kit DS1104.